Outward-Orientation and Development: Are Revisionists Right - T. N. Srinivasan; Jagdish Bhagwati (Yale University, Economic Growth Center, 1999)
The costs of import substitution (IS) as a strategy for industrialization, which was deemed synonymous with economic development by many development economists of the fifties and sixties, were shown to be substantial in the influential and nuanced studies of the seventies and eighties under the auspices of OECD, NBER and World Bank. These studies played a critical role in shifting policies in several developing countries away from the IS strategy. Recently there has been a proliferation of cross country regressions as a methodology of analysis of issues relating to growth, trade and other issues. Both proponents (e.g. Sachs and Warner (1995)) and opponents (Rodriguez and Rodrik (1999)) of the view that openness to trade is linked to higher growth have relied on such regressions. The paper systematically reviews the theoretical and empirical studies on such linkage. It rejects the cross-country regression methodology for reasons of their weak theoretical foundation, poor quality of their data base and their inappropriate econometric methodologies. It argues that the most compelling evidence on this issue can come only from careful case studies of policy regimes of individual entries such as those of OECD, NBER and World Bank. It concludes that the virtues of openness established in these nuanced in-depth studies remain unrefuted.
Keywords: E13; F11; F14; F43; 330; Developing Countries; Economic Development; Economic Growth; International Trade; Openness; Import Substitution; Export Promotion; Cross-Country Regressions; Handelsliberalisierung; Exportdiversifizierung; Importsubstitution; Wirtschaftswachstum; Theorie; Entwicklungsländer